The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1128/aac.00794-10
|View full text |Cite
|
Sign up to set email alerts
|

In VitroMitochondrial Toxicity of Metacavir, a New Nucleoside Reverse Transcriptase Inhibitor for Treatment of Hepatitis B Virus

Abstract: Therapy with nucleoside reverse transcriptase inhibitors (NRTIs) can be associated with mitochondrial toxicity. In vitro studies have been used to predict the predisposition for and characterize the mechanisms causing mitochondrial toxicity. Metacavir (PNA) is a novel synthetic nucleoside analog for oral administration with potent and specific antiviral activity against hepatitis B virus (HBV). We assessed the potential for mitochondrial toxicity of PNA in long-term cultures of HepG2 hepatoma cells by measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Then cells were fixed with 2.5% glutaraldehyde in 0.1 M phosphate buffer (pH7.2) at 4 C for 1 h and subsequently postfixed with 2% osmium tetroxide as described previously. 70 Then cells were dehydrated with sequential washes in ethanol and then embedded in Epon812 (SPI, 02660-AB). The samples were then sectioned with a Reichert-Jung ultracut E ultramicrotome 701704 (Leica, Germany) and stained with uranyl acetate and lead citrate.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Then cells were fixed with 2.5% glutaraldehyde in 0.1 M phosphate buffer (pH7.2) at 4 C for 1 h and subsequently postfixed with 2% osmium tetroxide as described previously. 70 Then cells were dehydrated with sequential washes in ethanol and then embedded in Epon812 (SPI, 02660-AB). The samples were then sectioned with a Reichert-Jung ultracut E ultramicrotome 701704 (Leica, Germany) and stained with uranyl acetate and lead citrate.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…As reported previously, metacavir did not have a high risk for potential mitochondrial‐related effects in rhesus monkeys after 3 months of intravenous administration (Zeng et al ., ), and no adverse effect was observed in rhesus monkeys which had been repeatedly dosed with 50 mg/kg per day for 6 months (Chen et al ., ). It is reported that the potential ability of metacavir to interfere with mitochondrial functions is low in vitro (Zhang et al ., ). In addition, treatment with metacavir for 3 months did not alter mitochondrial enzyme activity or mtDNA content in Himalayana marmotas (Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The antiviral activity of 2 0 ,3 0 -dideoxyguanosine (DoG) against human immunodeficiency virus (HIV) has been examined since 1990 (Busso et al 1990;Jeffrey et al 2014). DoG has also been demonstrated to have anti-duck hepatitis B virus (DHBV) efficacy in vivo (Chen et al 2007) and a favorable safety profile compared to AZT (Zeng et al 2009;Zhang et al 2010Zhang et al , 2011. However, its antiviral activity against different hepadnaviruses remains unclear.…”
Section: Introductionmentioning
confidence: 99%